Comparing two different methods of identifying alcohol related problems in the emergency department: a real chance to intervene?. Issue 2 (1st March 2001) - Hadida, A; Kapur, N; Mackway-Jones, K; Guthrie, E; Creed, F
Abstract : Objectives —To examine the feasibility of screening for alcohol problems in a representative flow sample of patients attending a busy UK emergency department. To compare two methods of identifying alcohol related problems in the emergency department. Methods —Brief interview administered by the same interviewer to a representative flow sample of 429 patients attending a single accident and emergency department over a six week period. Measures included a CAGE questionnaire and assessments by the patient and staff as to whether the attendance was alcohol related. Results —413 patients (96%) were successfully screened. Of these, 115 (28%) patients were considered to have an alcohol related attendance on the basis of the CAGE questionnaire or the staff assessment. Head injuries and psychiatric presentations were particularly likely to be associated with alcohol misuse. Compared with those identified by staff, patients scoring above threshold on the CAGE were more likely to attend during routine working hours and recognise they had an alcohol problem. Conclusions —Emergency departments may provide an opportunity for the early prevention of alcohol related difficulties. However, patients with alcohol problems who present to the emergency department are not a homogenous group. Different screening methods identify different groups of patients, who in turn may respond to different forms of intervention. Further research examining the efficacy and feasibility of different alcohol treatment approaches is needed to enable us to target specific interventions to those patients who might most benefit.